The Efficiency of Melinjo (Gnetum gnemon L.) Chip Supply Chain in Bantul District, Province of Yogyakarta - Sunendar Sunendar; Dwidjono Hadi Darwanto; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
Melinjo chip is one of the typical foods in Yogyakarta made of melinjo nuts. The production center of melinjo chip is located in Banguntapan and Pajangan Sub Districts, Bantul District. The purpose of this study is to determine the efficiency of the supply chain measured with transportation model analysis. The number of respondents in this research was 50 producers of melinjo chip in Bantul District, taken by simple random sampling method. While the snawball sampling method was used to get 5 (five) collector traders, 5 (five) large traders and 26 (twenty six) melinjo chip retailers that taken by following melinjo chip sales distribution from the producer to Market of Piyungan, Demangan, Kotagede, Sentul, Beringharjo, Bantul, Legi, and Magelang. The supply chain actors of melinjo chip are melinjo farmers, melinjo chip producers, collecting traders, large traders, retailers, consumers, packaging producers, production workers, haulers, and firewood providers. The analysis of transportation model with minimum cost illustrates that Wirokerten Village from Banguntapan Sub District allocate the production of melinjo chip to Market of Beringharjo and Piyungan, while Potorono Village allocates the to Market of Demangan. Sendangsari and Triwidadi Village from Pajangan Sub District allocate the production of melinjo chip to Market of Beringharjo, while Guwosari Village allocates to Market of Beringharjo, Bantul, and Legi.